SISTEM INFORMASI VEGETASI MANGROVE (SIVM) BERBASIS WEB DI TAMAN NASIONAL KARIMUNJAWA, JEPARA, JAWA TENGAH - sukmawati Nur Endah; Retno Kusumaningrum (Department of Informatics, Universitas Diponegoro, 2010)
Mangrove forest at Karimunjawa National Park that has been used for research, education source, and tourism, needs an information system accessible for global community. The information covers the species, morphology, and taxonomy of mangrove vegetations in Karimunjawa National Park. Human need for up to date and accurate information supported with modern technology motivates the researcher to construct mangrove vegetations information system web based. It is hoped that the information can be accessed by interest group. Methods to be used refers to the stage of system development method. Its name is FAST system. SIVM can be used for all social stratum because this output is easy to understand interesting and user friendly. Keywords: information system web based, mangrove vegetations